Autonomous, miniature research station (lab-payload) for the nanosatellite biological mission: LabSat - Patrycja Śniadek; Agnieszka Krakos; Adrianna Graja; Bartosz Kawa; Rafał Walczak; Jan Dziuban (Scientific Reports)
Abstract There is an increase in demand for bio-nanosatellites and biomedical methodologies as a result of experiments conducted in microgravity and radiation conditions. Currently, the latest trend is to replace the experiments carried out by cosmonauts at the International Space Station (ISS) with research performed with the use of autonomous payload for nanosatellite. This paper describes the lab-payload for a biological nanosatellite of the CubeSat type with a size of 2U (10 × 10 × 20 cm3). The proposed payload enables the long-term cultivation of two different biological experiments simultaneously and provides suitable growth conditions. This lab-payload is equipped with lab-chips dedicated to each of the cultures, a container with a nutrient solution, a medium dosing system, an optical detection system, lighting, a heating system and sensors for measuring temperature, humidity, pressure and radiation inside a thermos.